Potensi Ekowisata Bedengan Dalam Mendukung Pembangunan Berkelanjutan - Ola , Yohanes Maria Vianey; Widyastuti, Diena; Sulastri, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Bedengan Forest Tourism is an ecotourism destination renowned for its captivating natural scenery and rich cultural assets. This region is not only valued for its productive agricultural capacity but also serves as an excellent site for various nature-based tourism activities. Located in Selorejo Village, Dau District, Malang Regency, East Java, the research was undertaken in Bedengan from May to June 2025. The study aimed to identify the ecotourism potential of Bedengan, assess the role of the local community in supporting ecotourism, and develop strategies for sustainable ecotourism growth. The research employed survey and observation methods, with samples selected through purposive sampling. Data were analyzed qualitatively using SWOT analysis. The development strategies formulated based on the SWOT analysis include: (a) maximizing the appeal of Bedengan’s natural resources to promote educational nature tourism, supported by facilities such as ticket booths, prayer rooms, gazebos, toilets, parking, photo spots, camping gear, QR and educational parks, information boards, seating, flying fox, trash bins, and information centers; (b) expanding collaborations for educational and tourism promotions to enhance tourism management and visitor interest; and (c) proactively addressing potential threats by innovatively and characteristically developing Bedengan Tourism to ensure its long-term sustainability.